Organizational Commitment as a Bridge between Culture and Performance: A Study on Private University Lecturers in Batam - Rona Tanjung; Armansyah; Sumardin (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Organizational commitment is vital for enhancing lecturer performance in higher education institutions. This study examines the influence of transformational leadership and organizational culture on lecturer performance, mediated by organizational commitment, in a private university in Batam City. The research aims to understand how these factors interact and contribute to performance outcomes. A quantitative approach was employed, involving 75 active lecturers selected through simple random sampling. Data were collected using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling. The findings reveal that organizational commitment significantly enhances lecturer performance, while organizational culture directly influences both performance and commitment. Transformational leadership does not directly affect performance but significantly impacts organizational commitment. Notably, organizational commitment mediates the relationship between organizational culture and performance, but not between transformational leadership and performance. The study concludes that fostering a strong organizational culture and high commitment levels is essential for improving lecturer performance. Institutions should prioritize creating supportive work environments and leadership development programs to enhance commitment and performance, offering valuable insights for human resource management in higher education.